Sleep May Not Benefit Learning New Phonological Categories - Collet, Gregory; Schmitz, Rémy; Urbain, Charline; Leybaert, Jacqueline; Colin, Cécile; Peigneux, Philippe (Frontiers in Neurology, 2012)
It is known that sleep participates in memory consolidation processes. However, results obtained in the auditory domain are inconsistent. Here we aimed at investigating the role of post-training sleep in auditory training and learning new phonological categories, a fundamental process in speech processing. Adult French-speakers were trained to identify two synthetic speech variants of the syllable /də/ during two 1-hour training sessions. The 12-hours interval between the two sessions either did (8 p.m. to 8 a.m. ± 1h) or did not (8 a.m. to 8 p.m. ± 1h) included a sleep period. In both groups, identification performance dramatically improved over the first training session, to slightly decrease over the 12h offline interval, although remaining above chance levels. Still, reaction times were slowed down after sleep suggesting higher attention devoted to the learned, novel phonological contrast. Notwithstanding, our results essentially suggest that post-training sleep does not benefit more than wakefulness to the consolidation or stabilization of new phonological categories.